ANALISIS LAPORAN KEUANGAN PADA PT. NIDEC INDONESIA BINTAN DI TANJUNGPINANG TAHUN 2015-2018 - Alfi Hendri; Satriadi (JURNAL CAFETARIA, 2021)
This research is motivates by the phenomena that writer found from Baintan Anugerah Bersama Company’s financial statements which is shows the fluctuative performance from 2015-2018. Cash flows statement’s also have the fluctuative report’s in positive and negative values that we can analyze about the company’s financial performance. This research is a descriptive qualitative research that give some descriptions about the object of it’s research includes Balance Sheet, Income Statement and Cash Flow Statement. Data collection technique is from documentary and literature study. Data will analyze by Horizontal Analysis, Vertical Analysis, Cashflows Analysis and Profitability Analysis to measure financial statement’s performance. The result of this research that show us the financial statement’s performance of Baintan Anugerah Bersama company from 2015-2018 is good enough, but still need some evalutions from the management to increase their profitability because the profit margin averages under 2% and it still can increase by pushing their operational costs.